Analyzing Kumparan Green Initiative: A Model Of Digital Environmental Journalism - Muhammad Darisman; Nadiroh; Ananto Kusuma Seta (Program Studi Magister Manajemen Lingkungan, 2026)
This paper explores Kumparan Green Initiative as an emerging model of digital environmental journalism in Indonesia. The study examines how Kumparan integrates sustainability communication, storytelling, and audience participation in promoting the Sustainable Development Goals (SDGs). Using qualitative content analysis, this research reviews articles and campaigns published between 2024 and 2025, focusing on narrative techniques, issue framing, and public engagement. The results show that Kumparan initiative adopts a constructive and collaborative approach that enhances public understanding of environmental issues while inspiring behavioral change. This initiative contributes theoretically to the field of environmental communication and practically to the development of media-based sustainability education.